2020
DOI: 10.1038/s41598-020-77065-3
|View full text |Cite
|
Sign up to set email alerts
|

The expression of circadian clock genes in Daphnia magna diapause

Abstract: Diapause is a mechanism necessary for survival in arthropods. Often diapause induction and resurrection is light-dependent and therefore dependent on the photoperiod length and on the number of consecutive short-days. In many organisms, including the microcrustacean Daphnia magna, one functional entity with the capacity to measure seasonal changes in day-length is the circadian clock. There is a long-standing discussion that the circadian clock also controls photoperiod-induced diapause. We tested this hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The nocturnal feeding rhythm shown in D. dentifera is temperature compensated and is consistent with the well-studied DVM behavior of many zooplanktons. Circadian rhythms in Daphnia have been shown to impact behavior and life history traits (Coldsnow et al, 2017; Gust et al, 2019; Schwarzenberger et al, 2020). The observed circadian rhythm in feeding behavior could alter the timing of energetically demanding processes like metabolism and immunity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nocturnal feeding rhythm shown in D. dentifera is temperature compensated and is consistent with the well-studied DVM behavior of many zooplanktons. Circadian rhythms in Daphnia have been shown to impact behavior and life history traits (Coldsnow et al, 2017; Gust et al, 2019; Schwarzenberger et al, 2020). The observed circadian rhythm in feeding behavior could alter the timing of energetically demanding processes like metabolism and immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we evaluate whether there is a circadian rhythm in feeding behavior in Daphnia dentifera , a dominant primary consumer in North American temperate lakes. Prior studies have indicated that Daphnia have core clock genes and circadian expression of melatonin, immune, and sensory genes (Cellier-Michel et al, 2003; Bentkowski et al, 2010; Bernatowicz et al, 2016; Schwarzenberger and Wacker, 2015; Schwarzenberger et al, 2020, 2021). Daphnia are a model system for studying circadian rhythms in feeding behavior because they reproduce clonally, making individuals genetically identical, and quantifying individual feeding rates is relatively simple (Hite et al, 2020).…”
mentioning
confidence: 99%
“…Points in time were selected based on previously established cell number curves over time for both embryo types ( Chen et al, 2018 ). Successful resurrection was determined with the help of explicit morphological features (i.e., the appearance of the antennal buds, red and black eyes; Schwarzenberger et al, 2020 ). We chose five representative stages during embryonic development in D. magna asexually produced embryos and nine comparable stages in sexually developing embryos ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Daphnia are dominant herbivores and serve as keystone species by linking primary producers with secondary consumers in freshwater systems [ 7 ]. Daphnia are an ideal system for addressing if and how feeding behavior and microbial composition are linked because (1) they have a relatively simple microbiome, which has been characterized in multiple species [ 8 , 9 ], (2) they have core clock genes and show circadian expression of feeding behavior, immune, and sensory genes [ 10 13 ], and (3) quantifying individual feeding behavior is straightforward [ 14 ].…”
Section: Introductionmentioning
confidence: 99%